2016
DOI: 10.1097/bsd.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Safety and Clinical Outcomes Between Multiple-level and Single-level Cervical Disk Replacement for Cervical Spondylosis

Abstract: On the basis of this meta-analysis, clinical outcomes of multiple-level CDR are similar to those of single-level CDR for cervical spondylosis, which suggests the multiple-level CDR is as effective and safe as the single-level CDR. Nonetheless, more well-designed studies are needed for further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…These results could be because both cohorts have similar comorbidities overall. Our outcomes are consistent with previous literature that found no significant 30-day complications between inpatient versus outpatient CDR20,25–27 as well as studies that found no significant differences in 90-day complications between single versus multiple outpatient CDR 21…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results could be because both cohorts have similar comorbidities overall. Our outcomes are consistent with previous literature that found no significant 30-day complications between inpatient versus outpatient CDR20,25–27 as well as studies that found no significant differences in 90-day complications between single versus multiple outpatient CDR 21…”
Section: Discussionsupporting
confidence: 92%
“…With outpatient CDR gaining greater popularity as a treatment option for cervical pathologies requiring disk replacement, understanding the efficacy and safety of this outpatient procedure is necessary. Prior studies have investigated 30-day complication rates and found no significant differences in complication rates between patients who receive a single-level or multiple-level CDR in the inpatient setting compared with the outpatient setting 20,25–27. One study looking at 90-day complication rates of outpatient CDR only compared single-level outpatient CDR to multiple-level outpatient CDR without comparing the groups to inpatient CDR cohorts 27.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior approach was technically easier and allows decompression of the entire cervical spine [13]. In the multiple levels of cervical spondylosis with myelopathy patients who fail with conservative treatment, the choices of operative treatment may be anterior or posterior surgical management [20]. The spinal surgeons should be concerned about post-operative cervical kyphosis or postoperative loss of lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…55 These additional complications were not reported under AEs in each RCT, and were therefore not discussed in the present review. 3,56…”
Section: Discussionmentioning
confidence: 99%
“…55 These additional complications were not reported under AEs in each RCT, and were therefore not discussed in the present review. 3,56 Methods Clarity and Results Quality Quantifying the risk for AEs following CDA is essential to both patients and surgeons during the informed consent process. Heterogeneity in the quality and clarity of AE reporting has been documented in other spinal surgery cohorts.…”
Section: Anderson Et Al (2008) Bryanmentioning
confidence: 99%